2018
DOI: 10.11621/pir.2018.0109
|View full text |Cite
|
Sign up to set email alerts
|

The influence of student ethnicity on teacher expectations and teacher 
perceptions of warmth and competence

Abstract: Background. Previous research shows that incorrect teacher expectations about students can affect students' academic success. Moreover, students' ethnicity was found to be one of the most influential characteristics affecting teacher expectations, which can be based on ethnic stereotypes. Most studies test this relationship by comparing teacher expectations of multiple ethnic groups; however, we propose here another perspective, assuming that the connection between ethnic stereotypes and expectations may be de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
(66 reference statements)
1
1
0
1
Order By: Relevance
“…Although warmth may be important in regards to people’s behavior toward another person, such as approach – avoidance (Fiske et al, 2002), only competence was associated with expectations concerning the scholastic achievement of the students. This is in line with previous research (Akifyeva and Alieva, 2018), showing that expectations of academic proficiency of students belonging to a minority group are associated with teachers’ perceptions of competence, not warmth. These findings confirm the complexity of the relationships between stereotypical beliefs and behavior.…”
Section: Discussionsupporting
confidence: 93%
“…Although warmth may be important in regards to people’s behavior toward another person, such as approach – avoidance (Fiske et al, 2002), only competence was associated with expectations concerning the scholastic achievement of the students. This is in line with previous research (Akifyeva and Alieva, 2018), showing that expectations of academic proficiency of students belonging to a minority group are associated with teachers’ perceptions of competence, not warmth. These findings confirm the complexity of the relationships between stereotypical beliefs and behavior.…”
Section: Discussionsupporting
confidence: 93%
“…B. Akifyeva und Alieva 2018;Ferguson 2003); sie wirken sich somit auch auf die Aspirationen aus (Brind et al 2008). Gleichzeitig können Lehrer*innen Informationen, die über die Bewertung durch Schulnoten hinausgehen (etwa hohe Motivation oder Unterstützungspotenzial der Eltern) für ihre Einschätzungen heranziehen.…”
Section: K 3 Daten Und Methodenunclassified
“…The expectation of teachers can be defined as the assumptions and theories a teacher holds about their student's abilities, potential, and performance both in the long and short-term using a variety of sources, including the student's cognitive level, such as academic achievements and IQ level, non-cognitive characteristics, like behaviours and attitudes, their background attributes, which include their ethnicity, gender, socioeconomic status, etc. (Akifyeva & Alieva, 2018).…”
Section: A Teacher's Expectations and Beliefsmentioning
confidence: 99%
“…The lifestyle patterns of different groups are directly related to differences in their values and expectations (Hanel et al, 2018). Akifyeva and Alieva (2018) found that differences between ethnicities and expectations suggest the emergence of stereotypes. Stereotypes can be defined as a person's expectations, thoughts, and beliefs about certain characteristics toward all members of a group (Fiske, 2015).…”
Section: Introductionmentioning
confidence: 99%